Indústria cultural, ideologia, modelagem e totalitarismo: a função do influencer digital na beleza padronizada - Amaral, Luciano Campos de (2022)
In this dissertation, with a theoretical-bibliographic methodological characteristic, we focus the reflections from the Critical Theory of the Frankfurt School, especially Adorno and other authors who dialogue with this perspective. We aim to present in what sense the digital influencers of Instagram, as a product of the cultural industry, contribute to legitimize a standard of beauty that shapes and removes the autonomy of the individual, presenting a false cultural formation. For this, we review concepts present in the dynamics of work in capitalist society; we reflect on how Instagram digital influencers promote a standardization (technical manipulation as conditioning) of the subjects' way of thinking and acting that extends to their body and; we analyze the process of aesthetic construction of the subjects' body in this capital society in a process of totalitarian, pseudo-conscious, standardizing and standardized modeling. When studying these theorists we saw that from the authoritarian personality - through the manipulative subject that influences behaviors, desires and wills, we realize that these individuals model and control the subjects' bodies through the cultural industry, social media, social networks and Instagram. Thus, we are faced with the death mask and society as an appearance in the standardization of individuals' bodies, legitimizing a pseudoconscious beauty standard. Thus, these cultural elements modify the way subjects think, but, on the other hand, we also observe that these cultural elements are important in communication. However, in the current conjuncture these cultural elements have a single purpose, the sale and consumption of images and objects advertised by digital influencers on their social networks that influence thousands of individuals in their purchasing decisions. In this sense, the cultural industry uses physical activity, including leisure, to keep the subject connected at all times so that he does not have time to think. On the other hand, we have the concept of beautiful in the view of the world and of digital influencers in which people do not create, but copy other people's images into their lives. The ugly, the contradictory of the beautiful, determines the evaluations of people who leave the standard of beauty established by social media, social networks and Instagram. Digital influencers are the ones who choose what people will wear, drink, eat and do, achieving results of standardized bodies, in which people “are no longer themselves”, as the death mask operates the fitting in life, both in the routine of the digital influencer as in the lives of its consumers. The death mask fits into what the digital influencer uses in her daily life, but it also fits into the lives of her countless followers/consumers, which takes place through modeling and a totalitarian, pseudoconscious and deforming beauty standard.